2021
DOI: 10.1371/journal.pone.0247233
|View full text |Cite
|
Sign up to set email alerts
|

Colony-stimulating factor 3 signaling in colon and rectal cancers: Immune response and CMS classification in TCGA data

Abstract: Colorectal cancer is the 2nd leading cause of cancer-related deaths in the world. The mechanisms underlying CRC development, progression, and resistance to treatment are complex and not fully understood. The immune response in the tumor microenvironment has been shown to play a significant role in many cancers, including colorectal cancer. Colony-stimulating factor 3 (CSF3) has been associated with changes to the immune environment in colorectal cancer animal models. We hypothesized that CSF3 signaling would c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…CSF3R is a type 1 cytokine receptor, encoding the receptor for granulocyte colony-stimulating factor (G-CSF) and playing a crucial role in granulocyte proliferation and differentiation (64,65). The altered CSF3R expression or activating heterozygous variants in CSF3R have been identified as risk factors in the development of multiple malignancies, such as colorectal cancer, myeloid malignancies and lymphoid malignancies (65)(66)(67). This is particularly the case for mutations in CSF3R commonly present in chronic neutrophilic leukaemia or atypical chronic myeloid leukaemia (68).…”
Section: Discussionmentioning
confidence: 99%
“…CSF3R is a type 1 cytokine receptor, encoding the receptor for granulocyte colony-stimulating factor (G-CSF) and playing a crucial role in granulocyte proliferation and differentiation (64,65). The altered CSF3R expression or activating heterozygous variants in CSF3R have been identified as risk factors in the development of multiple malignancies, such as colorectal cancer, myeloid malignancies and lymphoid malignancies (65)(66)(67). This is particularly the case for mutations in CSF3R commonly present in chronic neutrophilic leukaemia or atypical chronic myeloid leukaemia (68).…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathway include immune system [69], neutrophil degranulation [70], cytokine signaling in immune system [71], extracellular matrix organization [72], post-translational protein phosphorylation [73], biological oxidations [74], metabolism [75] and metabolism of lipids [76] were responsible for progression of CD. CXCL5 [77], CXCL3 [78], PROK2 [79], CXCR1 [80], PYCR1 [81], OSM (oncostatin M) [82], IL15RA [83], LRG1 [84], LCN2 [85], BATF2 [86], CXCL1 [87], S100A9 [88], IFITM1 [89], MYOF (myoferlin) [90], XBP1 [91], MMP3 [92], TAP1 [93], FPR2 [94], CXCL6 [95], C2CD4A [96], IFITM3 [97], IL1B [98], SLC6A14 [99], FPR1 [100], NOS2 [101], CHI3L1 [102], TGM2 [103], MUC4 [104], TREM1 [105], WNT5A [106], HGF (hepatocyte growth factor) [107], CXCL9 [108], GBP1 [109], S100A11 [110], ADM (adrenomedullin) [111], CXCL11 [112], CXCL10 [113], LILRB2 [114], GDF15 [115], IL1RN [116] STAT1 [117], SLAMF7 [105], CYP27B1 [118], NETO2 [119], TFPI2 [120], ZC3H12A [121], MMP1 [122], CSF3 [123], SOCS3 [124], TLR8 [125], HTRA3 [126], CEBPB (CCAAT enhancer binding protein beta) [127], CD55 [128], CXCR2 [129], CCL28 [130], CBR3 [131], CCL3 [132], FCGR2A [48], ACSL1 [133], CCL2 [134], SOD2 [135], CD14 [136], IGFBP2 [137], CD274 [138], DERL3 [139], SERPINE1 [140], IDO1 [141], PDK...…”
Section: Discussionmentioning
confidence: 99%
“…The macrophage inflammatory protein-2 (MIP-2), also known as the CXCL2, is a critical chemokine for neutrophils that is produced in the rat intestine in response to platelet-activating factor (PAF) and to mediate intestinal inflammation and injury [29].CSF3 is a co-stimulator of inflammation and autoimmunity and is associated with changes to the immune environment in colorectal cancer animal models [30]. This study showed that CXCL2 and CSF3genes were downregulated in the TRF-treated group compared to the LPS-only group.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that CXCL2 and CSF3genes were downregulated in the TRF-treated group compared to the LPS-only group. Inhibition of these genes reduced inflammation in several diseases [30].…”
Section: Discussionmentioning
confidence: 99%